2020
DOI: 10.1155/2020/8851964
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Setup Employed in the Operating Room Based on Virtual and Mixed Reality: Analysis of Pros and Cons in Open Abdomen Surgery

Abstract: Currently, surgeons in operating rooms are forced to focus their attention both on the patient’s body and on flat low-quality surgical monitors, in order to get all the information needed to successfully complete surgeries. The way the data are displayed leads to disturbances of the surgeon’s visuals, which may affect his performances, besides the fact that other members of the surgical team do not have proper visual tools able to aid him. The idea underlying this paper is to exploit mixed reality to support s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 28 publications
4
37
0
Order By: Relevance
“…(2) e difference of hemoglobin before and after operation: laparoscopic group: 8.97 ± 7.52 (g/L) and open group: 13.06 ± 11.07 (g/L) (P � 0.044). (3) e average number of pelvic lymph nodes removed in the laparoscopic group was 21.83 ± 11.93, and that in the laparotomy group was 19.16 ± 10.24 (P � 0.391). e average number of para-aortic lymph nodes removed in the laparoscopic group was 3.66 ± 2.23, and that in the open group was 2.66 ± 1.73 (P � 0.387).…”
Section: Experimental Analysis On Endogenous Nitric Oxide Metabolism Of Sevoflurane Versus Propofol In Laparoscopicmentioning
confidence: 90%
See 1 more Smart Citation
“…(2) e difference of hemoglobin before and after operation: laparoscopic group: 8.97 ± 7.52 (g/L) and open group: 13.06 ± 11.07 (g/L) (P � 0.044). (3) e average number of pelvic lymph nodes removed in the laparoscopic group was 21.83 ± 11.93, and that in the laparotomy group was 19.16 ± 10.24 (P � 0.391). e average number of para-aortic lymph nodes removed in the laparoscopic group was 3.66 ± 2.23, and that in the open group was 2.66 ± 1.73 (P � 0.387).…”
Section: Experimental Analysis On Endogenous Nitric Oxide Metabolism Of Sevoflurane Versus Propofol In Laparoscopicmentioning
confidence: 90%
“…In recent years, a large number of foreign scholars have made excellent research on the effect of sevoflurane compared with propofol on endogenous nitric oxide metabolism in laparoscopic surgery. Bagia et al used a large number of experimental research methods in its research, compared different patients in the experimental group and the control group using sevoflurane and propofol, and concluded that the use of this drug in laparoscopic surgery can greatly reduce the side effects of patients and improve the therapeutic effect [2,3]. Chambers et al used case comparison method to compare the drug use of different groups of patients in different course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The mental and physical workload of users with regard to the use of these applications could be determined using a NASA-TLX (Task Load Index) questionnaire (Turini et al, 2018). Similarly, the ultimate system usability or user's interest/ enjoyment could be analyzed by means of the System Usability Scale (SUS) (Gregory et al, 2018) or the Intrinsic Motivation Inventory (IMI) scale (Galati et al, 2020), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The applications were developed using the Mixed Reality Toolkit development kit for Unity, which has become the standard for developing any MR application with HoloLens devices. This has been used in many medical applications for rhinoplasty (Maasthi et al, 2020), arthroplasty training (Turini et al, 2018), and open abdominal surgery (Galati et al, 2020). Loading of preoperative imaging studies with Digital Imaging and Communication on Medicine (DICOM) format was performed using a customised version of the Fellow Oak DICOM toolkit (Al-Zu'bi et al, 2017).…”
Section: Mixed Reality Frameworkmentioning
confidence: 99%
“…By exploiting our expertise in smartglasses-based open abdomen surgeries [ 7 ], we have used MR in the operating rooms for remote mentoring of the medical staff under training during Covid-19 pandemic. The study evaluates the implementation of MR in the cancer surgeries carried out at the IRCCS Hospital ‘Giovanni Paolo II’ in the city of Bari (Italy).…”
Section: Introductionmentioning
confidence: 99%